(untitled) (Pakistan Journal of Scientific Research, 2023)
The requirement engineering process is the initial and critical phase of the software development life cycle. Project success heavily depends on requirements elicitation and their management. Requirement change management is a vital aspect of requirement engineering. Incomplete understanding among stakeholders, technological shifts, functional improvements, and evolving business landscapes often trigger requirements changes. Continuous changes demand meticulous tracking and effective management to prevent project failure. Implementing a formalized approach to requirements change management is essential for controlling the impact of changing system requirements. Through surveys, interviews, and literature review, it becomes evident that within Pakistan software industry, numerous barriers hinder software engineers from effectively managing and addressing end-user change requests. Our solution addresses the challenges of requirement changes, emphasizing cost and time estimates. We recommend the RCM tool, which is user-friendly, free, and centralizes requirements. Access controls restrict project details to relevant team members, while versioning and notifications keep stakeholders informed. Organizing changes by SDLC phases aids analysis and learning. Overall, our solution promotes efficient, transparent requirement management within the SDLC framework and increases the success rate by managing change requests effectively.